2022
DOI: 10.1155/2022/2156424
|View full text |Cite|
|
Sign up to set email alerts
|

Correlation of Serum Chemokine (C-C Motif) Ligand 21 and Heat Shock Protein 90 with Preeclampsia

Abstract: Objective. The study aimed to explore the correlation of serum chemokine (C-C motif) ligand 21 (CCL21) and heat shock protein 90 (Hsp90) with preeclampsia (PE). Methods. Between June 2021 and June 2022, 50 pregnant women with PE were included in the PE group, and 50 healthy pregnant women were included in the control group. The serum levels of CCL21 and Hsp90 were compared between the two groups. Results. PE patients showed significantly higher levels of CCL21 and Hsp90 than healthy pregnant women … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
1
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%